2008
DOI: 10.1007/s11202-008-0109-6
|View full text |Cite
|
Sign up to set email alerts
|

Computing the test rank of a free solvable Lie algebra

Abstract: We computed the test rank of a free solvable Lie algebra of finite rank.An element g of an algebra (group) G is a test element if each endomorphism ϕ of G keeping g invariant is an automorphism; i.e., ϕ(g) = g implies that ϕ is an automorphism.A natural generalization of the notion of test element is the notion of test set. Let G be an n-generated algebra (group). The set of elements {g 1 , . . . , g m }, m ≤ n, is called test if, for every endomorphism ϕ of G and i = 1, . . . , m, the conditions ϕ(g i ) = g i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…The following more general result was proved in [18] Lemma 5.3. Let S 2d be a free solvable group of rank 2 and class d ≥ 2 with basis z 1 , z 2 , and let v ∈ S (d−1) 2d…”
Section: Description Of Verbally and Algebraically Closedmentioning
confidence: 91%
See 2 more Smart Citations
“…The following more general result was proved in [18] Lemma 5.3. Let S 2d be a free solvable group of rank 2 and class d ≥ 2 with basis z 1 , z 2 , and let v ∈ S (d−1) 2d…”
Section: Description Of Verbally and Algebraically Closedmentioning
confidence: 91%
“…It is likely that the answer to this question is negative. By Timoshenko's theorem (see [18] or [19]) the test rank of S rd , r, d ≥ 2, is r − 1. Recall, that test rank of a group G is the minimal number of elements of G such that every endomorphism fixing any of this elements is automorphism.…”
Section: Description Of Verbally and Algebraically Closedmentioning
confidence: 99%
See 1 more Smart Citation
“…It turns out that the test rank of a free polynilpotent Lie algebra is either equal to the rank of the Lie algebra or is one less than the rank of it. Interest in the test ranks of free soluble Lie algebras is explained in [13] and [15]. Temizyurek and Ekici [13] showed that a free soluble Lie algebra of rank 2 with solvability class 3 has test rank 1 and pointed out the particular test element for such algebras.…”
Section: Introductionmentioning
confidence: 99%
“…Temizyurek and Ekici [13] showed that a free soluble Lie algebra of rank 2 with solvability class 3 has test rank 1 and pointed out the particular test element for such algebras. The test rank for free soluble Lie algebras of solvability class greater than 3 is calculated by Timoshenko and Shevelin in [15] and it is shown that the test rank of a free soluble Lie algebra of rank n ≥ 2 is equal to n − 1.…”
Section: Introductionmentioning
confidence: 99%